2018
DOI: 10.3892/ol.2018.8961
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Wilms' tumor 1 expression in patients with pancreatic ductal adenocarcinoma

Abstract: The only current curative treatment for patients with pancreatic ductal adenocarcinoma (PDA) is surgical resection, and certain patients still succumb to disease shortly after complete surgical resection. Wilms' tumor 1 (WT1) serves an oncogenic role in various types of tumors; therefore, in the present study, WT1 protein expression in patients with PDA was analyzed and the association with overall survival (OS) and disease-free survival (DFS) time in patients with PDA was assessed following surgical resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Kanai T et al, found in their study that the median DFS time for patients with PDA with weak and moderate to strong cytoplasmic WT1 expression was 543 and 196 days, respectively. 6 The differential diagnosis between primary mucinous epithelial ovarian cancers and mucinous metastasis from other organs also relies on other clinical characteristics including bilaterality, surface involvement, signet ring cell presence, and lympho vascular invasion, which are more common in metastases and quite rare in primary mucinous ovarian cancers. 3,4 There is still a certain proportion of tumors for which, based on the morphological and immunohistochemical (IHC) features alone, the distinction between a primary and a metastatic tumor is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Kanai T et al, found in their study that the median DFS time for patients with PDA with weak and moderate to strong cytoplasmic WT1 expression was 543 and 196 days, respectively. 6 The differential diagnosis between primary mucinous epithelial ovarian cancers and mucinous metastasis from other organs also relies on other clinical characteristics including bilaterality, surface involvement, signet ring cell presence, and lympho vascular invasion, which are more common in metastases and quite rare in primary mucinous ovarian cancers. 3,4 There is still a certain proportion of tumors for which, based on the morphological and immunohistochemical (IHC) features alone, the distinction between a primary and a metastatic tumor is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have studied expression patterns of WT1 in pancreatic cancer [46,47]. However, only one recent study evaluated the prognostic value of WT1 in pancreatic ductal adenocarcinoma, indicating that cytoplasmic overexpression of WT1 correlated with unfavourable prognosis for the patient [48]. Notwithstanding, these findings were based on a small cohort of only 50 patients and additional studies would be necessary to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…The Wilms' tumor 1 (WT1) gene was originally isolated as a gene responsible for pediatric kidney neoplasm and had been regarded as a tumor suppressor gene (18). However, a number of researchers consider the WT1 gene to serve an oncogenic role in leukemia (19)(20)(21)(22) and a wide variety of solid tumors (23)(24)(25) based on the results reported by our group and other groups (26)(27)(28). The WT1 protein is highly immunogenic (29).…”
Section: Introductionmentioning
confidence: 99%